Obrońca nienarodzonych - ŚLĘCZKA, Piotr (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
In the ethics worked out by the late Tadeusz Styczeń, SDS, a special position is given to the right to life belonging to every unborn baby. In his philosophical analyses Styczeń demonstrates the way to discover the personal dignity of a baby before his or her birth. The beginning of a human being, which results from the conception of the new life in question, for reasons of logic and rationality must be tantamount to the origin of the personal dignity of this human individual. No other approach to this issue is rationally acceptable since it is impossible to point, in the process of the development of an already existing life, to a single moment when the existence of a «non−human» being transforms into the existence of a human being. Since every unborn baby is a person who cannot defend his or her right to life, he or she needs special protection in state law. However, in many states, including democratic ones, the situation is reverse: the law does not protect the lives of the unborn. Styczeń describes this situation as a veiled totalitarianism in which the principle of equality of all before the law is violated. In the theological aspect, Styczeń associated the dignity of human life with the fact that life is always a gift from the Creator, its ultimate source, who in way shares his own being with every human. In the article, three fields have been distinguished in which Styczeń was striving for protection of and respect for the lives of the unborn, namely, his academic career, his social involvement and his concern about the proper interpretation of the teaching of the Catholic Church about the dignity of life. Translated by Dorota Chabrajska